Diffusive phase transformations in metallic glasses - Louzguine, Dmitri V. (Diffusion Fundamentals, 2017)
A large set of experimental results obtained by the author and colleagues related to the diffusionrelated effects and phase transformation observed in metallic glasses will be presented and discussed.